Gut microbiota diversity repeatedly diminishes over time following maintenance infliximab infusions in paediatric IBD patients. - Katrine Carlsen; Louise B Thingholm; Astrid Dempfle; Mikkel Malham; Corinna Bang; Andre Franke; Vibeke Wewer (PLoS ONE)
Background The gut microbiome plays a crucial role in the pathogenesis and progression of inflammatory bowel disease (IBD). Understanding the dynamics of the gut microbiome in relation to treatment can provide valuable insights into disease management and therapy strategies. The aim of this study is to investigate if diversity and composition of the gut microbiome correlate with time since treatment and disease activity during maintenance infliximab (IFX) therapy among children with IBD. Methods Data was collected from IBD patients aged 10-17 participating in an IFX-eHealth study. IFX infusions were administered in 4-12-week intervals based on weekly faecal calprotectin (FC) combined with symptom scores. Excess stool samples underwent microbiome profiling using 16S rRNA gene sequencing. Microbiome features, including alpha diversity and single taxa, were analysed for three key variables: 1) weeks-since-treatment, 2) FC, and 3) symptom score. Results From 25 patients (median age 14.4 years) diagnosed with Crohn´s Disease (n = 16) or ulcerative colitis (n = 9), microbiota were analysed in 671 faecal samples collected across 15 treatment intervals. A significant decrease over time in Shannon diversity, following the initial increase within four weeks of treatment, was found across patients. FC levels showed no association with alpha diversity (p>0.1), while symptom scores showed a negative association with Shannon and observed diversity in patients with UC. At the genus level, a lower abundance of the genera Anaerostipes and Fusicatenibacter (Firmicutes), and a greater abundance of the genus Parasutterella (Proteobacteria), were associated (p.adj<0.05) with the time elapsed since last infusion in UC specifically, while only Parasutterella was associated across the full cohort (p.adj = 1e-10). Conclusions We found a recurring reduction over time in alpha diversity following the initial increase in diversity after an IFX infusion. Changes in an individual's microbiome may be an early sign of increasing disease activity that precedes clinical symptoms and increased FC.